The new platinum(IV) derivative LA-12 shows stronger inhibitory effect on Hsp90 function compared to cisplatin - Kvardova, Veronika; Hrstka, Roman; Walerych, Dawid; Muller, Petr; Matoulkova, Eva; Hruskova, Veronika; Stelclova, Dagmar; Sova, Petr; Vojtesek, Borivoj (Molecular cancer, 2010)
BACKGROUND: Cisplatin and its derivatives are commonly used anti-cancer drugs. However, cisplatin has clinical limitations including serious side effects and frequent emergence of intrinsic or acquired resistance. Thus, the novel platinum(IV) complex LA-12 represents a promising treatment modality, which shows increased intracellular penetration resulting in improved cytotoxicity in various cancer cell lines, including cisplatin resistant cells. RESULTS: LA-12 disrupts cellular proliferation regardless of the p53 status in the cells, however the potency of the drug is greatly enhanced by the presence of a functional p53, indicating several mechanisms of action. Similarly to cisplatin, an interaction of LA-12 with molecular chaperone Hsp90 was proposed. Binding of LA-12 to Hsp90 was demonstrated by Hsp90 immunoprecipitation followed by platinum measurement using atomic absorption spectrometry (AAS). An inhibitory effect of LA-12 on Hsp90 chaperoning function was shown by decrease of Hsp90-assisted wild-type p53 binding to p21WAF1 promoter sequence in vitro and by accelerated ubiqutination and degradation of primarily unfolded mutant p53 proteins in cells exposed to LA-12. CONCLUSIONS: To generalize our findings, LA-12 induced degradation of other Hsp90 client proteins such as Cyclin D1 and estrogen receptor was shown and proved as more efficient in comparison with cisplatin. This newly characterised molecular mechanism of action opens opportunities to design new cancer treatment strategy profitable from unique LA-12 properties, which combine DNA damaging and Hsp90 inhibitory effects.
Keywords: imunoprecipitace; Spectrophotometry, Atomic; Humans; proteiny tepelného šoku HSP90; amantadin; cisplatina; Cisplatin; spektrofotometrie atomová; nádorový supresorový protein p53; Antineoplastic Agents; Blotting, Western; lidé; HSP90 Heat-Shock Proteins; Organoplatinum Compounds; Cyclin-Dependent Kinase Inhibitor p21; nádorové buněčné linie; protinádorové látky; organoplatinové sloučeniny; Cell Line, Tumor; Immunoprecipitation; western blotting; inhibitor p21 cyklin-dependentní kinasy; Amantadine; Tumor Suppressor Protein p53